Effect of Trehalose on Cryopreservation of Hariana Bull Spermatozoa - Kumar, Gyanesh; Yadav, Dileep Kumar; Saxena, Atul; Sachan, Vikas; Kumar, Anuj; Swain, Dilip Kumar; Yadav, Brijesh (Indian Journal of Veterinary Sciences and Biotechnology, 2023)
The present experiment was designed to study the effect of supplementation of Trehalose on freezability and antioxidant activity of Hariana bull semen. Semen samples were diluted in TFYG extender containing different concentrations of Trehalose (10mM, 30mM & 50mM). The control samples were extended with TFYG alone. Results clearly indicated that, 30 mM Trehalose group had significantly (P<0.05) higher percentage of individual motility, sperm viability, & higher percentage of intact acrosome in comparison to the control and other Trehalose supplemented groups. In biochemical assays, no clear-cut demarcation for antioxidant enzyme was found for Trehalose supplementation. However, Trehalose supplementation has showed increase activity for Glutathion reductase (GR). The results obtained clearly indicated that supplementation of Trehalose to extender prior to cryopreservation improves Hariana bull sperm quality.